10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
This qualitative study aimed to explore the experience of fear of missing out (FoMO) among parents of children with cancer during the caregiving period, and to examine the manifestations of FoMO, its triggering factors, and its underlying relationship with fundamental psychological needs. 14 parents hospitalized in the pediatric ward were purposively recruited. A descriptive phenomenological qualitative study was conducted using face-to-face, semi-structured interviews. Guided by the Self-Determination Theory, 3 main themes-obstacles to autonomous participation, deficits in competence, and insufficient relational connections-and 8 subthemes were identified. The perspectives of the parents revealed a multi-layered anxiety related to the fear of missing critical opportunities and support. Healthcare professionals should pay attention to this unique anxiety subtype and develop systematic support networks to restore parents' sense of autonomy, competence, and relatedness, thereby effectively alleviating their FoMO.